Diseño de un sistema de recolección para la evacuación de las aguas residuales de la comunidad de San Cristóbal, Cantón Paute, Provincia del Azuay. - Ayón Regalado, Luis Antonio (2025)
The project focuses on the design of a wastewater collection and treatment system in the parish of San Cristóbal, canton Paute, with the objective of mitigating public health problems and environmental contamination. It is proposed that 13.11% of the population suffers from water-related diseases, which justifies the need for an adequate system. For its development, corrugated PVC pipes and manholes were used, following technical standards. The results indicate that the implementation of the system will not only improve water quality, but will also contribute to local economic development by attracting investment. The conclusions highlight the urgency of building the system to improve public health and the environment, in line with population growth projections. It is recommended to prioritize construction, conduct educational campaigns on waste management, and establish a maintenance program to ensure the long-term operability of the system. Keywords: Wastewater, public health, infrastructure, sustainable development, San Cristobal.